2000
DOI: 10.1016/s0045-6535(99)00310-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an enzyme-linked immunosorbent assay (ELISA) to gas chromatography (GC) – measurement of polychlorinated biphenyls (PCBs) in selected US fish extracts

Abstract: Robert O., "Comparison of an enzymelinked immunosorbent assay (ELISA) to gas chromatography (GC) -measurement of polychlorinated biphenyls (PCBs) in selected US fish extracts" (1999). USGS Comparison of an enzyme-linked immunosorbent assay (ELISA) to gas chromatography (GC) ± measurement of polychlorinated biphenyls (PCBs) AbstractThe analysis of PCBs in ®sh tissues by immunoassay methods was evaluated using ®sh collected from a US monitoring program, the National Contaminant Biomonitoring Program of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Concentrations of 1.0 -3.2 g/g in individual 1995 samples and station means Ͼ 0.3 g/g occurred at NCBP Stations 24 (Ohio R. at Marietta, OH), 23 (Kanawha R. at Nitro, WV), 67 (Allegheny R.), 76 (Mississippi R. at Memphis), 111 (Mis-sissippi R. at Lake City, MN), 26 (Illinois R.), 28 (Arkansas R.), 70 (Ohio R. at Metropolis, IL), 27 (Mississippi R. at Guttenburg, IA), 112 (Mississippi R. at Dubuque, IA), 25 (Cumberland R. at Clarksville, TN), and 15 (Mississippi R. at Luling, LA; Figure 7). At most of these sites, mean concentrations either declined substantially (Stations 23,81,111,and 24) or did not change appreciably since the mid-1980s (Schmitt et al 1999c;Zajicek et al 2000; data not shown). Lee and Anderson (1998) also reported declining PCB concentrations in carp and walleye from urbanized areas of the MRB in Minnesota during 1975-95.…”
Section: Pcbsmentioning
confidence: 93%
See 1 more Smart Citation
“…Concentrations of 1.0 -3.2 g/g in individual 1995 samples and station means Ͼ 0.3 g/g occurred at NCBP Stations 24 (Ohio R. at Marietta, OH), 23 (Kanawha R. at Nitro, WV), 67 (Allegheny R.), 76 (Mississippi R. at Memphis), 111 (Mis-sissippi R. at Lake City, MN), 26 (Illinois R.), 28 (Arkansas R.), 70 (Ohio R. at Metropolis, IL), 27 (Mississippi R. at Guttenburg, IA), 112 (Mississippi R. at Dubuque, IA), 25 (Cumberland R. at Clarksville, TN), and 15 (Mississippi R. at Luling, LA; Figure 7). At most of these sites, mean concentrations either declined substantially (Stations 23,81,111,and 24) or did not change appreciably since the mid-1980s (Schmitt et al 1999c;Zajicek et al 2000; data not shown). Lee and Anderson (1998) also reported declining PCB concentrations in carp and walleye from urbanized areas of the MRB in Minnesota during 1975-95.…”
Section: Pcbsmentioning
confidence: 93%
“…However, the toxicity of individual PCB congeners ranges over several orders of magnitude (Ahlborg et al 1994;van den Berg et al 1998) and varies with the endpoint being considered (Hansen 1998). The congener composition of weathered PCBs also varies greatly among NCBP locations and taxa (Zajicek et al 2000). Toxicity of PCB congeners and other dioxin-like compounds occurs through multiple mechanisms, both aryl hydrocarbon hydroxylase (AhR) and non-AhR-mediated.…”
Section: Pcbsmentioning
confidence: 99%
“…Finally, recent techniques derived from the H4IIE cell bioassay (e.g., H4IIE cell lines transfected with AhR-responsive reporter genes) will be compared to the original bioassay. Other in vitro methods of estimating PHH concentrations in environmental samples exist (Roberts and Durst, 1995;Zajicek et al, 2000), but comparisons of these techniques with the H4IIE cell bioassay are beyond the scope of our review. The goal of this review is to provide the reader with an understanding of how and why the H4IIE cell bioassay has been used.…”
Section: E the H4iie Cell Linementioning
confidence: 99%
“…These assays have a sensitivity reaching the picogram level and were found to show a response roughly proportional to the toxic potency of the analysed congeners [9,26]. Dioxin and PCB immunoassays have been successfully applied to the analysis of soil, water, fly ash and biological tissue extracts, although examination of the last of these usually requires rather extensive sample preparation [26,27,28]. The correlation between dioxin equivalents derived from chemical analytical measurements or derived from immunoassays were found to be reasonably good.…”
Section: Immunoassaysmentioning
confidence: 98%
“…For instance, in a screening study on the dioxins and furans in fly ash from a municipal waste incinerator, Focant et al reported r 2 -values of 0.84 for the correlation between MS/MS analytical data and immunoassay data [29]. For PCB levels in fish extracts, Zajicek et al found an r 2 -value of 0.75 [28]. A good correlation (r 2 = 0.92) between chemical (GC/MS) determinations and immunoassay results was also reported in a study on dioxin compounds in human milk [30].…”
Section: Immunoassaysmentioning
confidence: 99%